Byrudite, (Be, 〈)(V3+, Ti)3O6, a new mineral from the Byrud emerald mine, South Norway. (2nd January 2018) - Raade, G.; Balić-Žunić, T.; Stanley, C. J.
Abstract: Byrudite (IMA 2013-045, Raade et al ., 2013), with simplified formula (Be, 〈)(V 3+, Ti)3 O6, occurs in emerald-bearing syenitic pegmatites of Permian age at Byrud farm, Eidsvoll, Akershus, South Norway. It has a norbergite-type structure, Pnma, with a = 9.982(1), b = 8.502(1), c = 4.5480(6) Å, V = 385.97(9) Å3, Z = 4. The structure was refined to R 1 = 0.045 for 1413 unique reflections. Twinning occurs on 210. The occupancy of the tetrahedral Be site refined to 0.84(1). The presence of Be was verified by secondary ion mass spectrometry but could not be quantified. Electron-microprobe analyses of the crystal used for structure determination gave the empirical formula (Be0.84 〈0.16 ) (V1.32 3+ Ti1.25 Cr0.29 Fe0.09 Al0.07 )Σ3.02 O6 . There is a strong inverse correlation between V and Cr. The ideal endmember formula is BeV2 3+ TiO6 . The mineral is black and opaque with a metallic lustre. Reflectance data in air are reported from 400 to 700 nm. The Commission on Ore Mineralogy required wavelengths are [ R 1, R 2 (λ in nm)]:16.6, 17.5(470), 16.7, 17.9(546), 16.8, 18.3(589) and 16.8, 18.6(650). The Mohs hardness is ∼7, based on indentation measurements. The mineral is brittle with an uneven fracture; cleavage is not present. D (calc.) = 4.35 g cm –3 for the empirical formula with 0.84 Be a.p.f.u. The strongest reflections of the calculated powder X-ray diffraction pattern are [ d in Å (Irel )( hkl )]: 3.721(72)(111), 2.965(100)(121), 2.561(50)(311), 2.464(41)(230), 2.167(24)(231), 1.681(34)(402), 1.671(66)(232), 1.435(23)(630).